Implementation of eco-friendly behavior by front office employees to support green hotel at The Ritz-Carlton Bali - Kadek Isa Engelita Dewi; Ni Ketut Bagiastuti; I Ketut Sutama; Ni Luh Ayu Kartika Yuniastari Sarja (Politeknik Negeri Bali, 2022)
This study aimed to find out the implementation of Eco-friendly behavior by front office employees to support the Green hotel at The Ritz-Carlton Bali, Indonesia, and the influence of the implementation. The data collection method used was by conducting field observations, distributing questionnaires with saturated samples to 40 employees in the front office department as respondents and interviews with the Assistance front office Manager of The Ritz-Carlton Bali. The data analysis techniques used are descriptive statistical and simple linear regression analysis techniques to answer the problem formulation in this study. All the tests was carried out with measurements using IBM SPSS Statistics 26 for windows application. The results of the analysis show that the implementation of Eco-friendly behavior by front office employees as a whole is already within very high criteria. There are 2 implementations that still on high criteria and are still not very optimal, namely prioritizing using stairs over elevators and disposing of garbage according to their type. The implementation of Eco-friendly behavior has a positively strong relationship and has a significant effect on the green hotel.